THE INTERNATIONAL MIGRATION AND ITS EFFECTS AT THE EUROPEAN AND NATIONAL LEVEL - Flavia Andreea Murtaza (Annals of the University of Craiova: Economic Sciences Series, 2019)
In the following, the author proposes to analyze the context of the workforce migration, as well as the remittances, a phenomenon occurring in parallel with the population migration. The thesis starts with the description of the determining factors of a person that decides to leave his/her native country. The author also presents some general aspects on migration and remittances, emphasizing at the same time the impact of the remittances on the economic development of a country. The immigrants and their families are key-factors in the economic growth as long as the remittances are efficiently used, not only for consumption, but more for investments, savings or the development of entrepreneurship, which emphasizes and brings forward the financial inclusion of these population segments, that is the immigrants and their families. Romania that meets the economic conditions of being considered the source of migration is presented as an example